Processing, microstructure and property aspects of a spraycast Al-Mg-Li-Zr - Hogg, S; Palmer, I; Thomas, L; Grant, P (2007)
This paper describes a microstructural and property investigation of an Al-5.31Mg-1.15Li-0.28Zr alloy produced by spraycasting and downstream processing. Following a dispersoid precipitation treatment of 4 h at 400 °C, samples were hot compressed at strain rates of 2, 1, 0.2 and 0.1 × 10-2 s-1 at temperatures between 250 and 475 °C. Electron backscattered diffraction showed a strong dependence of recrystallised grain size on deformation temperature. At 250 °C and faster strain rates at 325 °C, a network of fine recrystallised necklace grains formed by progressive lattice rotation. At 325 °C at slow strain rates and at 400 °C and higher, dynamic recrystallisation occurred by discontinuous nucleation and growth at regions of microscopic strain localisation such as grain boundaries and triple points. The microstructures from small-scale hot compression experiments were compared with larger forgings under similar conditions and microstructural evolution was broadly similar. Mechanical properties of larger-scale forgings exceeded the targets for mechanically alloyed Al-Mg-Li alloy AA5091. © 2006 Acta Materialia Inc.